1997
DOI: 10.1046/j.1365-2141.1997.2703087.x
|View full text |Cite
|
Sign up to set email alerts
|

BCL6 gene rearrangements also occur in marginal zone B‐cell lymphoma

Abstract: Summary.Marginal zone B-cell lymphoma (MZBCL) represents a distinct subtype of B-cell non-Hodgkin's lymphoma (NHL) which has been recently recognized and defined as a disease entity. Cytogenetically, these lymphomas reveal a high prevalence of trisomy 3, and recent data obtained by comparative genomic hybridization indicate that the chromosomal regions 3q21-23 and 3q25-29 might be of particular pathogenetic significance. We identified structural chromosomal abnormalities involving the region 3q27 and rearrange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 34 publications
0
24
0
2
Order By: Relevance
“…The translocations that have been described in NMZL do not include regions harboring these genes. 12,15,76,77,79,82,[85][86][87][88][89] Although Dierlamm and colleagues did not detect translocations involving BCL6 in NMZL, 12,20,77 the karyotypes of 3 of 21 patients described by TraverseGlehen et al do suggest translocations involving BCL6. …”
mentioning
confidence: 88%
See 1 more Smart Citation
“…The translocations that have been described in NMZL do not include regions harboring these genes. 12,15,76,77,79,82,[85][86][87][88][89] Although Dierlamm and colleagues did not detect translocations involving BCL6 in NMZL, 12,20,77 the karyotypes of 3 of 21 patients described by TraverseGlehen et al do suggest translocations involving BCL6. …”
mentioning
confidence: 88%
“…[9][10][11][12][13][14][15][16][17][18][19][20] Both sexes are affected with approximately equal frequency.…”
Section: Introductionmentioning
confidence: 99%
“…Part of these cases was included in previous studies. 5,7,9,[14][15][16][17] Gastric endoscopic biopsies were included in this study on condition that clonal Ig heavy chain rearrangement was demonstrated to support the diagnosis of a MALT lymphoma. All cases were reviewed and diagnosed as extranodal marginal zone lymphomas according to the recent criteria of the WHO.…”
Section: Case Selectionmentioning
confidence: 99%
“…Several genes located at chromosome 3 have been proposed as possibly responsible for these alterations, including BCL6 and FOXP1. 31,40,[45][46][47][48] Given that the BCL6 gene is involved in diffuse large B-cell lymphomas, it is possible that this gene also contributes to the pathogenesis of other lymphomas with trisomy 3, but the actual target gene in MALT lymphoma with trisomy 3 has not yet been identified. Recently, p16 gene methylation was detected in 60% of MALT lymphoma cases, and it was also suggested that p16 methylation is not associated with tumor progression, but may be an early event in MALT lymphomagenesis.…”
Section: Molecular Genetics Of Mucosa-associated Lymphoid Tissue Lympmentioning
confidence: 99%